Neuropsychological characteristics of adults with attention‐deficit/hyperactivity disorder without intellectual disability. Issue 4 (30th August 2020) - Hida, Masami; Hayashi, Wakaho; Okajima, Yuka; Takashio, Osamu; Iwanami, Akira
Abstract: Aims: While several studies have reported various cognitive impairments in children with attention‐deficit/hyperactivity disorder, the neuropsychological profiles of adults with this disorder are understudied. Here, the intelligence and memory functions of adults with attention‐deficit/hyperactivity disorder without intellectual disability were evaluated. Methods: The Wechsler Adult Intelligence Scale—Third Edition and Wechsler Memory Scale—Revised were administered to 30 adults with attention‐deficit/hyperactivity disorder whose full‐scale intelligence quotients were >85. Diagnoses were based on the Diagnostic and Statistical Manual of Mental Disorders‐IV criteria. Conners' Adult ADHD Rating Scales—Self‐Report—screening version and the Autism Spectrum Quotient were also evaluated. Results: In the Wechsler Adult Intelligence Scale—Third Edition, the verbal intelligence quotient was significantly higher than the performance intelligence quotient and the verbal comprehension score was the highest among the secondary indices. In the Wechsler Memory Scale—Revised, the visual memory score was the highest measure. Although the verbal intelligence quotient had no correlation with any Wechsler Memory Scale—Revised measures, the performance intelligence quotient was significantly correlated with the visual memory and attention scores of the Wechsler Memory Scale—Revised. Conners' Adult ADHD Rating Scales hyperactive‐impulsive score was significantly correlated with the verbal intelligence quotient, whereas the inattention score was not correlated with any measures of the Wechsler Adult Intelligence Scale—Third Edition or Wechsler Memory Scale—Revised. Conclusions: The results suggest that while adults with normal‐intelligence attention‐deficit/hyperactivity disorder have comparatively high verbal comprehension and social knowledge, their ability of information processing and visual‐motor coordination are relatively weak. Abstract : The Wechsler Adult Intelligence Scale—Third Edition (WAIS‐III) and Wechsler Memory Scale—Revised (WMS‐R) of 30 adults with attention‐deficit/hyperactivity disorder (ADHD) were examined. The verbal intelligence quotient was significantly higher than the performance intelligence quotient in the WAIS‐III and the performance intelligence quotient was significantly correlated with the visual memory and attention scores of the WMS‐R. Adults with ADHD have comparatively high verbal comprehension and social knowledge, while their information processing ability and visual‐motor coordination are relatively weak.